Drying characteristics of starch-gelatin edible films plasticized with glycerol: article / Nordiyana Aisyah Mohammad Nordin, Norasmah Mohammed Manshor - Mohammad Nordin, Nordiyana Aisyah; Mohammed Manshor, Norasmah (2017)
The uncontrolled waste solid to the landfill cause researcher to invent more biodegradable product. A starch-gelatin based film is one of the product to improve the solid waste management for food and pharmaceutical industry. The main objective for this research project is to prepare starch-gelatin films containing glycerol at different temperature and to determine the drying characteristics of the starch-gelatin based films. The film was prepared by mixing the gelatin powder, potato and glycerol into distilled water at 90oC for 30 minutes. Then the film is casted on plate and dried at temperature 45, 50, 55 and 60oC. The film is weight every one hour until reaches equilibrium moisture content. Three model of drying kinetic was used. The models are Newton, Page, Henderson and Pabis models. The best model chosen based on value coefficient of correlation (R2) closer to 1, root mean square error (RMSE) and reduce chi square (χ2) closer to 0. The best model is Newton model at 45oC.